Alzheimer's Disease Genes Are Associated with Measures of Cognitive Ageing in the Lothian Birth Cohorts of 1921 and 1936. (14th May 2011) - Hamilton, Gillian; Harris, Sarah E.; Davies, Gail; Liewald, David C.; Tenesa, Albert; Starr, John M.; Porteous, David; Deary, Ian J.
Abstract : Alzheimer's disease patients have deficits in specific cognitive domains, and susceptibility genes for this disease may influence human cognition in nondemented individuals. To evaluate the role of Alzheimer's disease-linked genetic variation on cognition and normal cognitive ageing, we investigated two Scottish cohorts for which assessments in major cognitive domains are available: the Lothian Birth Cohort of 1921 and the Lothian Birth Cohort of 1936, consisting of 505 and 998 individuals, respectively. 158 SNPs from eleven genes were evaluated. Single SNP analyses did not reveal any statistical association after correction for multiple testing. One haplotype from TRAPPC6A was associated with nonverbal reasoning in both cohorts and combined data sets. This haplotype explains a small proportion of the phenotypic variability (1.8%). These findings warrant further investigation as biological modifiers of cognitive ageing.